On the performance of adaptive modulation in cellular systems - Xiaoxin Qiu; Chawla, K. (IEEE transactions on communications, 1999)
Adaptive modulation techniques have the potential to substantially increase the spectrum efficiency and to provide different levels of service to users, both of which are considered important for third-generation cellular systems. In this work, we propose a general framework to quantify the potential gains of such techniques. Specifically, we study the throughput performance gain that may be achieved by combining adaptive modulation and power control. Our results show that: (1) using adaptive modulation even without any power control provides a significant throughput advantage over using signal-to-interference-plus-noise ratio (SINR) balancing power control and (2) combining adaptive modulation and a suitable power control scheme leads to a significantly higher throughput as compared to no power control or using SINR-balancing power control. The first observation is especially important from an implementation point of view. Adjusting the modulation level without changing the transmission power requires far fewer measurements and feedback as compared to the SINR-balancing power control or the optimal power control. Hence, it is significantly easier to implement. Although presented in the context of adaptive modulation, the results also apply to other variable rate transmission techniques, e.g., rate adaptive coding schemes, coded modulation schemes, etc. This work provides valuable insight into the performance of variable rate transmission techniques in multi-user environments.